(untitled) (Research, Society and Development, 2022)
Objective: To present, based on scientific literature, the role of nursing in promoting sexual health and its impact on the lives of adolescents. Methodology: This is an integrative literature review, carried out in the Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF) and Scientific Electronic Library Online (SCIELO) databases. articles written in Portuguese, published in the period between 2017 and 2021, were used. Results: A total of 308 articles were found, after methodological rigor through the inclusion and exclusion criteria, 14 articles were selected, 6 articles in LILACS, 4 in BDENF and 4 in SCIELO. The analysis of selected articles was descriptive and predisposed to the data extraction stage: author / year of publication, title / database and objective. Conclusion: According to the literature, it appears that sex education is of paramount importance for adolescents, considering that the lack of it causes negative impacts on the biopsychosocial aspects of this group. It is noteworthy that school is the best place to approach these adolescents to educate them about self-knowledge about their sexual option, how to prevent STIs and unplanned pregnancy.